3D printing in agriculture - review - Schné, Tamás; Jaskó, Szilárd (GEORGIKON FOR AGRICULTURE, 2023)
Additive Manufacturing techniques are more and more popular in the word. The most popular name of it is 3D printing. This solution is used in many different areas and applications. This work is a review that concentrate the applications of 3Dprinting in agriculture. The paper discusses the different tools and devices used in agricultural producing, sensors that can be used for process monitoring. In both fields There are many types of raw material that use in this technology, but the most popular at the PLA and the ABS. The popularity of these come from the low prise and the easy and many side usability. An interesting area of printable materials is the usage of agricultural wastes such as nut and crab shells, etc. An interesting usage of 3D printing when we are printing food. This should be helps for sick person who has swallowing problems or unique look at can be created with it for example for a restaurant.
Keywords: 3D printing; agriculture; food processing